Air toxics and early childhood acute lymphocytic leukemia in Texas, a population based case control study. Issue 1 (December 2016) - Symanski, Elaine; Tee Lewis, P.; Chen, Ting-Yu; Chan, Wenyaw; Lai, Dejian; Ma, Xiaomei
Abstract Background Traffic exhaust, refineries and industrial facilities are major sources of air toxics identified by the U.S. Environmental Protection Agency (U.S. EPA) for their potential risk to human health. In utero and early life exposures to air toxics such as benzene and 1, 3-butadiene, which are known leukemogens in adults, may play an etiologic role in childhood leukemia that comprises the majority of pediatric cancers. We conducted a population based case–control study to examine individual effects of benzene, 1, 3-butadiene and polycyclic organic matter (POM) in ambient residential air on acute lymphocytic leukemia (ALL) diagnosed in children under age 5 years in Texas from 1995–2011. Methods Texas Cancer Registry cases were linked to birth records and then were frequency matched by birth month and year to 10 population-based controls. Maternal and infant characteristics from birth certificates were abstracted to obtain information about potential confounders. Modelled estimates of benzene, 1, 3-butadiene and POM exposures at the census tract level were assigned by linking geocoded maternal addresses from birth certificates to U.S. EPA National-Scale Air Toxics Assessment data for single and co-pollutant statistical analyses. Mixed-effects logistic regression models were applied to evaluate associations between air toxics and childhood leukemia. Results In adjusted single pollutant models, odds of childhood leukemia among mothers with the highest ambient air exposures compared to those in the lowest quartile were 1.11 (95 % CI: 0.94–1.32) for POM, 1.17 (95 % CI: 0.98–1.39) for benzene and 1.29 (95 % CI: 1.08–1.52) for 1, 3-butadiene. In co-pollutant models, odds ratios for childhood leukemia remained elevated for 1, 3-butadiene but were close to the null value for benzene and POM. Conclusions We observed positive associations between 1, 3-butadiene and childhood leukemia in single and co-pollutant models whereas effect estimates from single pollutant models were diminished for benzene and POM in co-pollutant models. Early life exposure to 1, 3-butadiene rather than benzene or POM appears to increase early childhood risk of acute lymphocytic leukemia.